Bibliometric analysis of Spanish scientific collaboration between Psychology and other health areas between 1980 and 2019 - González-Sala, Francisco; Osca-Lluch, Julia; Ferragud, Carmel (Anales de Psicología / Annals of Psychology, 2024)
Knowing the collaboration between researchers from different areas is a way of determining the evolution of an epistemological area towards its own scientific status. The aim of this paper is to analyse the collaboration between psychology and health sciences through the analysis of scientific production according to different bibliometric indicators. We analysed 4.295 articles published between 1980 and 2019 in Web of Science journals (WoS), in which there was interdisciplinary collaboration between an author belonging to a Spanish institution in the area of psychology and a researcher belonging to other areas of the health sciences. The results show an increase in collaboration between psychology and health sciences throughout the years, with special relevance between clinical psychology and psychiatry and Neurosciences through the study of mental health. This collaboration is materialised through three axes, universities, hospitals and research institutes, with special relevance of the CIBERSAM groups, acting as a link between profession and research.